The Herpetofauna of Nallamala Hills, Eastern Ghats, India: An Annotated Checklist, With Remarks on Nomenclature, Taxonomy, Habitat Use, Adaptive Types and Biogeography - Srinivasulu, C.; Das, I. (Asiatic Herpetological Research, 2008)
We present an inventory of the herpetofauna of the Nallamala Hills, Eastern Ghats, south-eastern India. The fauna, as currently known, includes 20 species of amphibians belonging to 14 genera in six families and 64 species of reptiles belonging to 42 genera in 15 families.